THE EFFECT OF EDIBLE COATING OF CHITOSAN ON THE QUALITY OF TILAPIA (Oreochromis niloticus) FILLETS STORED AT LOW TEMPERATURES - Indra Muhammad Ridwan; Sukirno Mus; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was intended to determine the effect of using chitosan on tilapia(Oreochromis niloticus) fillets stored at low temperatures (5oC) and to determinethe best concentrate of chitosan using natural preservative on tilapia fillets. Theusing of research method was experimental method and the used design wasrandomized block design (RAK) at one factorial of wihch 4 varians wereconsentrate of chitosan solution K0 (0%), K1 (1%), K2 (1,5%), and K3 (2%).While as a block treatments were shelf life of 0, 5, 10, and 15 days. The 2% ofchitosan solution (K3) that was the superior treatment based on odor 7,44, TVB 28mgN/100gram, moisture 58,134%, fat 1,665%, protein 17,878%, pH 6,77 andTPC 4,45x105 coloni/gram on meat of tilapia fillets. While the organoleptic of 1,5% of chitosan solution (K2) was the superior treatment based on appreance 7,76and texture 7,56.Key words: Chitosan, tilapia fillets